A Patient-Clinician Discussion of Current Challenges in Schizophrenia Part 2: Negative Symptoms in Schizophrenia [Podcast] - Racher M; Carpenter W; Kane JM (Neuropsychiatric Disease and Treatment, 2023)
Matthew Racher,1 William Carpenter,2 John M Kane3 1National Alliance on Mental Illness, Arlington, Virginia, USA; 2University of Maryland School of Medicine, Maryland, USA; 3Zucker School of Medicine at Hofstra/Northwell, New York, USADr John Kane is Professor of Psychiatry and Molecular Medicine at the Donald and Barbara Zucker School of Medicine at Hofstra/Northwell, a recipient of the Arthur P. Noyes Award in Schizophrenia, the Lieber Prize for Outstanding Research in Schizophrenia, the Heinz E. Lehmann Research Award from New York State, and the Dean Award from the American College of Psychiatrists.Dr William Carpenter, MD, is a professor of psychiatry at the University of Maryland School of Medicine, is Editor-in-Chief for Schizophrenia Bulletin. Dr Carpenter’s main research focus is in the area of schizophrenia, and was awarded The Rhoda and Bernard Sarnat International Prize in Mental HeaCorrespondence: Dr John M Kane, Department of Psychiatry, 75-59 263rd Street, Kaufmann Building, Suite 103, Glen Oaks, New York, 11004, USA, Tel +1 718 4708141, Email JKane2@northwell.eduAbstract: Dr John Kane discusses negative symptoms in schizophrenia alongside fellow expert, Dr William Carpenter, and Mr Matthew Racher, a Certified Recovery Peer Specialist and dedicated advocate for people living with schizophrenia, who is currently studying for his Master of Social Work (MSW) in Miami, Florida. In this podcast, the authors discuss challenges and opportunities faced by patients and clinicians in the assessment and treatment of negative symptoms. They also touch upon emerging therapeutic strategies, with the aim of raising awareness of the unmet therapeutic needs of those living with negative symptoms. Mr Racher provides a unique patient perspective to this discussion, drawing on his own daily experiences of living with negative symptoms, as well as offering positive insights from his recovery from schizophrenia.Keywords: schizophrenia, negative symptoms, clinician and patient perspectives, peer support, psychosocial support, clinical assessment, treatments